PENGARUH UKURAN KAP, PROFITABILITAS, KOMITE AUDIT, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2009-2013 - GLARENDHY PRATAMA, HAKAM (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this research is to tempt and analyze the effect of KAP criterion, profitability, audit committee, company criterion, and leverage against audit delay. The population of this company use companies which listed on Indonesia Stock Exchange (BEI/IDX) 2009-2013 as much as 450 companies. The sample collection done with purposive of sampling, with this technique obtained the sample used in this research as many as 79 companies. This study use secondary data in the form of audit financial report and annual report from the website of Indonesia Stock Exchange (IDX).This study use five free variables which are a KAP size, profitability, audit committee, firm size, and leverage. Bound variable of this research is an audit delay. The method of analysis which used to examine free variables on bound variable is a double regression.The result show that KAP size variable measured by dummy influence to audit delay significantly. Another variables such as profitability variable which measure by ROA, audit committe variable which measure by KOMAU, firm size variable which measure by LnTA, and leverage variable which measure by DTAR. This result means that the profitability variable, audit committe, firm size, and leverage, there is no significant influence to audit delay. Keyword : KAP size, profitability, audit committee, firm size, leverage, and audit delay.